Effects of plasma treatment on the surface wettability of glass substrate - Hwang, Yi Hui (Nanyang Technological University, 2024)
In this study, the effects of O2 and 95% N2 with 5% H2 plasma treatment on surface wettability, topography and surface chemistry of glass microscopic slides were investigated utilizing contact angle goniometer, atomic force microscopy (AFM), UV-Vis spectroscopy and x-ray photoelectron spectroscopy (XPS). Directly after plasma treatment, the surfaces were completely wetted by water to determine the average contact angle. The average contact angle was recorded daily for the subsequent few days until superhydrophilicity was lost (above 10°), and hydrophobic recovery set in. The surface free energy can be increased significantly depending on the plasma treatment. However, an extended duration of plasma treatment does not necessarily result in prolonged superhydrophilicity. Therefore, the determination of optimal plasma treatment time proved crucial in achieving prolonged superhydrophilicity.